Gull-wing Stacked Profunda Artery Perforator Flap for Unilateral Breast Reconstruction - Hajime Matsumine, MD, PhD; Yosuke Niimi, MD, PhD; Hiroyuki Sakurai, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2025)
Summary:. The profunda artery perforator (PAP) flap, harvested from the medial aspect of the thigh, is increasingly used for breast reconstruction because of its low donor-site morbidity and ease of harvest. However, the PAP flap has a limited fat volume, which makes it difficult to use in women with larger breasts. To overcome this limitation, we have developed the “gull-wing stacked” PAP flap, which combines 2 PAP flaps with the aim of achieving adequate volume, projection, and aesthetic outcomes. We performed skin-sparing mastectomy followed by immediate reconstruction using 2 PAP flaps in 3 patients (aged 47–50 y) with unilateral breast cancer. Both thighs were used as donor sites. The flaps were sutured proximally and rotated in opposing directions, mimicking a gull-wing door motion, to create a rounded breast. The internal mammary vessels were chosen as the recipient vessels, with vascular anastomoses performed in an antegrade or retrograde manner. All flaps survived without vascular complications or the need for reoperation. The transferred tissue provided adequate volume and projection, eliminating the need for additional fat grafting. Aesthetic outcomes were deemed excellent in all cases. The gull-wing stacked PAP flap is a promising option for patients who are ineligible for an abdominal flap because of previous surgery or other factors. This method effectively replicates the shape of the breast using a unique flap configuration but requires an extended operation time and significant surgical staffing. Further studies are necessary to optimize the procedure and evaluate long-term outcomes.